Green Fish - Chang-dong, Lee; Yu Young-gil; Mun Seong-kun; Han Seong-kyu; Suk-kyu Han (Third Window Films, 2007)
Han Suk-kyu plays Mak-dong, a discharged soldier who returns home to find things have changed: his family has issues, work is difficult to find and the nearby city has grown. He meets a woman who takes a liking to him and she helps him get a job as part of a small gang, so he can earn money for his struggling family to live happily. Lee Chang-dong, with his debut feature, opts to tell this story with a moody, understated style to make it all the more real and evocative. [www.acdrifter.com]